Comparative Dentoskeletal Study of Class II Division 1 and Class II Division 2 Malocclusion Subjects - Dhakal, Jyoti (Orthodontic Journal of Nepal, 2011)
The dentoskeletal characteristics of Class II malocclusion subjects were evaluated using cephalometric radiograph and dental cast of 60 untreated patients. The sample included 30 Class II Division 1 and 30 Class II Division 2 malocclusion patients. The inter-canine, inter-premolar, inter-molar, inter-canine alveolar, inter-premolar alveolar, inter-molar alveolar widths are measured on study models. The result showed statistically significant difference between the groups for mandibular inter-canine width only. The cephalometric analysis revealed that SNB angle was responsible for the skeletal sagittal difference between the two groups except for the position of maxillary incisors. No basic difference in dentoskeletal morphology existed between Class II Division 1 and Class II Division 2 malocclusions.